Pengaruh Penggunaan E-Modul Hidrolisis Garam Berbasis Probem Based Learning dengan Pendekatan Teaching at the Right Level Terhadap Hasil Belajar Murid Kelas XI Fase F SMAN 5 Padang - Hasbia Husna Handriza; Iryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Salt hydrolysis is one of the chemistry topics taught in Grade XI Phase F that requires students to understand prerequisite concepts, including acid-base theory, ionic reactions, chemical equilibrium, solution concentration, and pH calculations. Based on an interview with a chemistry teacher at SMAN 5 Padang, approximately 50% of the students had not achieved the Learning Objectives Achievement Criteria (Kriteria Ketercapaian Tujuan Pembelajaran [KKTP]) in the salt hydrolysis topic. One effort to address this problem was the implementation of a salt hydrolysis e-module based on Problem-Based Learning (PBL) integrated with the Teaching at the Right Level (TaRL) approach, which had been developed and refined. This study aimed to analyze the effect of using the e-module on students' cognitive learning outcomes. A quasi-experimental method with a nonequivalent control group design was employed. The research sample consisted of 60 Grade XI students selected through purposive sampling and assigned to an experimental class and a control class, each comprising 30 students. The research instrument was a 25-item multiple-choice objective test. The data were analyzed using an independent samples t-test. The results showed that the mean posttest score of the experimental class was 88.53, which was higher than that of the control class (81.33). Furthermore, the independent samples t-test indicated that t value > t table (3.850 > 1.671, α = 0.05), indicating that the use of the PBL-based salt hydrolysis e-module integrated with the TaRL approach had a significant positive effect on students' cognitive learning outcomes.